AN EXPLORATION OF HEALTHY AGRICULTURAL PRODUCT DEVELOPMENT STRATEGIES WITHIN INDONESIAN SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) - Komalasari, Rita; Mustafa, Cecep (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
For the first time, this study aims to comprehensively explore the landscape of innovation and healthy product development within Indonesian Small and medium-sized enterprises (SMEs) in the food and drinks industry. By addressing existing gaps, the paper provides insights into the context-specific factors, the role of healthy product variants, and the interconnected dynamics that drive innovation. The research employs a thorough literature review. The literature review establishes the foundation by identifying gaps and theoretical frameworks, including the Innovation Ecosystem Theory, to guide the analysis. The findings illuminate several key contributions of this research. First, the study crystallizes the specific new product development practices within Indonesian SMEs, addressing the lack of context-specific insights. It highlights the significance of healthy product development within a changing consumer landscape. The analysis reveals diverse strategies, challenges, and successes, emphasizing the role of networking, creative innovation drivers, and the absence of financial constraints. Furthermore, the introduction of a unified framework for innovation provides a holistic understanding that bridges theoretical constructs and practical applications. This study identifies flaws in the current innovation policy, suggesting actionable recommendations for improvement. In conclusion, this paper fills critical gaps in the literature, offering a comprehensive exploration of innovation and healthy product development within Indonesian SMEs in the food and drinks industry. By integrating context-specific insights, addressing gaps, and providing practical value for stakeholders and policymakers, the research significantly advances our understanding of healthy agricultural product development.